PENGARUH KEGIATAN OUTBOUND STEPPING CARPET TERHADAP KECERDASAN INTERPERSONAL ANAK USIA 5-6 TAHUN DI TK BINA MANDIRI KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Miranti, Miranti; Risma, Devi; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of outbound stepping carpet on interpersonal intelligence in children aged 5-6 years in TK Bina Mandiri Rambah Hilir District Rokan Hulu District. The research used experimental method with one group pre-test post-test design. The sample used in this study were 18 students. The data collection technique used is observation. Technique of data analysis using t-test test by using program of SPSS 23. The research hypothesis is that there is influence of outbound stepping carpet toward interpersonal intelligence in children aged 5-6 years in TK Bina Mandiri Kecamatan Rambah Hilir Rokan Hulu Regency. Based on data analysis known tcalculated = 15,605> ttable = 2,110 with Sig. (2-tailed) = 0,000. Because Sig <0,05 it can be concluded that there are differences of interpersonal intelligence before and after done outbound stepping carpet. It can be interpreted that there is influence of outbound stepping carpet activity toward interpersonal intelligence in children aged 5-6 years in TK Bina Mandiri Subdistrict Rambah Hilir Rokan Hulu significant as much as 48.26%.Keyword: Interpersonal Intelligence, Outbound Stepping Carpet Activities